Preparation method of thermosetting adhesive capable of controlling debonding and application method of thermosetting adhesive in composite material bonding

By introducing dynamic acetal bonds into thermosetting adhesives and breaking them under acidic conditions, the controllable debonding of the adhesive is achieved, and the problem of difficulty in disassembling after bonding of thermosetting adhesives is solved, and it is highly efficient and controllable.

CN119662177APending Publication Date: 2025-03-21NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411964655.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Thermoset adhesives are difficult to depolymerize, dissolve or melt again after they are completely cured, resulting in the rapid disassembly and repair of the adhesive components during service period becoming a problem.

Method used

Acetal dynamic bonds are introduced into the crosslinking network structure of the thermoset adhesive, so that it can be controlledly broken under acidic conditions, destroying the crosslinking network, thereby achieving controllable debonding of the adhesive.

Benefits of technology

The controllable debonding of thermosetting adhesives under acidic conditions is achieved, and the problem of difficulty in effectively debonding and disassembling of traditional epoxy adhesives after bonding is solved. It has the characteristics of high initial bonding strength and rapid debonding.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662177A_ABST
    Figure CN119662177A_ABST
Patent Text Reader

Abstract

The invention discloses a controllable debonding thermosetting adhesive, a preparation method of the controllable debonding thermosetting adhesive and application of the controllable debonding thermosetting adhesive in bonding and disassembling of composite materials. The preparation method comprises the following steps: S1, reacting an aldehyde monomer with an alcohol monomer to obtain a polyhydroxy intermediate containing an acetal structure; the aldehyde monomer has at least one hydroxyl functional group; the alcohol monomer has more than three hydroxyl functional groups; s2, carrying out ring-opening addition and alkaline environment ring-closing epoxidation reaction on epoxy chloropropane and the polyhydroxy intermediate to obtain an epoxy monomer containing an acetal dynamic bond; and S3, mixing and curing the epoxy monomer obtained in the step S2 and an amine curing agent to obtain the controllable debonding thermosetting adhesive under the acidic condition. The thermosetting adhesive disclosed by the invention is high in initial bonding strength and quick in debonding under an acidic condition. A composite material joint bonded by using the thermosetting adhesive disclosed by the invention is high in bonding strength and convenient to disassemble and recycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of thermosetting adhesives, and in particular to a thermosetting adhesive capable of controllable debonding under acidic conditions, a preparation method thereof, and application of the thermosetting adhesive in bonding and disassembling of composite materials. Background Art

[0002] Thermosetting adhesives (such as epoxy, polyurethane, etc.) have excellent bonding properties, electrical insulation properties, chemical resistance, high temperature resistance and other characteristics. They are widely used in the fields of automobiles, electronics, wind power generation, aerospace, etc., and are the most widely used type of synthetic adhesives with the largest output. The three-dimensional cross-linked network structure of thermosetting adhesives gives them excellent cohesion and bonding strength, but it also makes it difficult for the adhesive to depolymerize, dissolve or melt again after it is fully cured, which brings huge challenges to the rapid disassembly, maintenance and efficient graded disassembly and recycling of bonded parts / components (such as carbon fiber composite parts in the aviation and wind power fields) during their service life.

[0003] Although people have introduced heat-expandable additives into thermosetting adhesive systems to make the adhesive physically / chemically expand under heat induction, forcing the adhesive to fail and providing a possible solution for the disassembly of bonded parts, this type of heat-disassembly adhesive also has the following shortcomings:

[0004] (1) It is difficult to completely disassemble and there is a lot of residual glue;

[0005] (2) Toxic and harmful gases are released during the expansion process;

[0006] (3) The process is uncontrollable and causes damage to the substrate;

[0007] (4) Additives have high chemical activity and their applications are limited.

[0008] An ideal controllable disassembly adhesive should have sufficient bonding strength in service, and be able to be disassembled in a controllable and convenient manner when disassembly is required. Therefore, the development of new adhesives with controllable bonding and debonding has attracted widespread attention.

[0009] Introducing dynamic chemical bonds that can break under external field stimuli such as light, heat, and pH into the cross-linked network structure of thermosetting adhesives provides a new idea for achieving reversible breaking and controllable debonding of the adhesive cross-linked network.

[0010] Dynamic chemical bonds refer to chemical bonds that undergo reversible breakage / reorganization under specific external field stimulation conditions (such as light, heat, and chemical stimulation) and can be used to construct various types of smart materials with stimulus-responsive behaviors.

[0011] At present, the basic principle of designing and preparing adhesives with controllable debonding is mainly to introduce dynamic chemical bonds into the cross-linked network structure of thermosetting adhesives. Based on the dynamic reversible characteristics of dynamic chemical bonds, the dynamic bonds are reversibly broken through external field stimulation to cause depolymerization and destruction of the cross-linked structure, and the cross-linking density is reduced, thereby achieving controllable dissociation of thermosetting adhesives and controllable disassembly of bonded parts.

[0012] Dynamic chemical bonds are divided into dynamic covalent bonds and dynamic non-covalent bonds. The dynamic covalent bonds currently used in removable adhesives mainly include Diels-Alder (DA) bonds, disulfide bonds, β-ester bonds, borate bonds and oxime ester bonds; dynamic non-covalent bonds mainly include hydrogen bonds, metal ligand complexes, π-π stacking, host-guest interactions, etc.

[0013] The present invention discloses a preparation technology of a novel controllable degradation debonding thermosetting adhesive containing an acetal structure, and an application method thereof in bonding composite material structural parts, providing a new idea and a new method for solving the problem that components of composite materials and other materials in the fields of aviation, wind power, electronics, electrical appliances, etc. are not easy to be disassembled again after being bonded with epoxy structural adhesive. Summary of the invention

[0014] The present invention provides a controllable debonding thermosetting adhesive under certain conditions, a preparation method thereof, and an application thereof in bonding and disassembling of composite materials. The present invention introduces acetal bonds as controllable debonding functional units into the cross-linked network structure of a thermosetting resin, and the resulting thermosetting adhesive has high initial bonding strength. Under acidic external stimulation (organic solvents can be added as an aid if necessary), the acetal bonds can be broken, the cross-linked network is destroyed, and the adhesive can be quickly debonded and disassembled, thereby achieving controllable debonding of the thermosetting adhesive under acidic conditions, solving the problem that the thermosetting adhesive is not easy to disassemble again after bonding.

[0015] The specific technical solutions are as follows:

[0016] [1] A method for preparing a thermosetting adhesive with controllable debonding, comprising the steps of:

[0017] S1, an aldehyde monomer and an alcohol monomer react to obtain a polyhydroxy intermediate containing an acetal structure; the aldehyde monomer has at least one hydroxyl functional group; the alcohol monomer has three or more hydroxyl functional groups;

[0018] S2, epichlorohydrin and the polyhydroxy intermediate undergo ring-opening addition and ring-closing epoxidation in an alkaline environment to obtain an epoxy monomer containing an acetal dynamic bond;

[0019] S3, mixing and curing the epoxy monomer obtained in step S2 with an amine curing agent to obtain a thermosetting adhesive with controllable debonding under acidic conditions.

[0020] In step S1, the aldehyde monomer may include but is not limited to at least one of aldehyde functional group-containing monomers such as vanillin and p-hydroxybenzaldehyde.

[0021] In step S1, the alcohol monomer may include but is not limited to at least one of polyol monomers such as glycerol, pentaerythritol, trimethylolpropane, and trimethylolethane.

[0022] In step S1, the aldehyde monomer and the alcohol monomer may be added according to a molar ratio of aldehyde group in the aldehyde monomer to the alcohol monomer of 1:1 to 1.5.

[0023] In step S1, the reaction temperature may be 80-100°C.

[0024] In step S1, the reaction solvent may be an organic solvent, which may include but is not limited to at least one of N,N-dimethylformamide (DMF) and petroleum ether.

[0025] In step S1, the reaction may be carried out in the presence of a catalyst. Further, the catalyst may include p-toluenesulfonic acid monohydrate and the like.

[0026] In step S2, the polyhydroxy intermediate and the epichlorohydrin can be added according to a molar ratio of hydroxyl groups in the polyhydroxy intermediate to the epichlorohydrin of 1:3-6.

[0027] In step S2, the reaction temperature of the ring-opening addition can be 80-120°C.

[0028] In step S2, the ring-opening addition may be carried out in the presence of a catalyst. Further, the catalyst may include tetrabutylammonium bromide or the like.

[0029] In step S2, the temperature of the alkaline environment ring-closing epoxidation reaction can be 30-60°C.

[0030] In step S2, the alkaline environment can be obtained by adding a sodium hydroxide aqueous solution. Optionally, the molar ratio of sodium hydroxide in the added sodium hydroxide aqueous solution to the hydroxyl group in the polyhydroxy intermediate is 4 to 10:1. Optionally, the mass percentage concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 30% to 60%.

[0031] In step S3, the amine curing agent may include but is not limited to at least one of isophoronediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, diethyltoluenediamine, 2,4,6-tris(dimethylaminomethyl)phenol, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfone and the like amine curing agents.

[0032] In step S3, the epoxy monomer obtained in step S2 and the amine curing agent can be mixed in a completely reactive stoichiometric ratio. The primary amine and the secondary amine in the amine curing agent can react with the epoxy group in the epoxy monomer obtained in step S2.

[0033] In step S3, no special requirements are made on the curing conditions, for example, the curing conditions generally required by amine curing agents in the art can be designed.

[0034] In some preferred examples, the aldehyde monomer is p-hydroxybenzaldehyde, and the alcohol monomer is trimethylolpropane, and the obtained thermosetting adhesive has a better initial bonding strength and is easier to debond under acidic conditions.

[0035] [2] A thermosetting adhesive with controllable debonding under acidic conditions prepared according to the preparation method described in [1]. The thermosetting adhesive with controllable debonding under acidic conditions described in the present invention is a thermosetting adhesive containing a three-dimensional dynamic cross-linked network.

[0036] [3] The use of the thermosetting adhesive capable of controlled debonding under acidic conditions according to [2] in bonding and disassembling fiber composite materials.

[0037] In some embodiments, the application described in [3], when the fiber composite material bonded by the controllable debonding thermosetting adhesive under acidic conditions is disassembled, the controllable debonding thermosetting adhesive under acidic conditions can be treated with acid to degrade and debond the controllable debonding thermosetting adhesive under acidic conditions. The acid used in the acid treatment may include but is not limited to at least one of hydrochloric acid, sulfuric acid, etc. Further, the controllable debonding thermosetting adhesive under acidic conditions can be treated with an acid solution containing an organic solvent. The controllable debonding thermosetting adhesive under acidic conditions described in the present invention can be rapidly degraded and debonded under acidic conditions with the assistance of an organic solvent. Furthermore, the organic solvent may include but is not limited to at least one of tetrahydrofuran, acetone, ethanol, etc.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The present invention introduces acetal dynamic bonds into the three-dimensional cross-linked network structure of the thermosetting adhesive, which can cause the acetal bonds to break under acidic conditions (organic solvents can be added as an aid if necessary), resulting in the destruction of the cross-linked network, thereby achieving controllable debonding of the thermosetting adhesive, solving the problem that traditional epoxy adhesives are difficult to effectively debond and disassemble after bonding.

[0040] The thermosetting adhesive of the present invention has high initial bonding strength and fast debonding under acidic conditions. The composite material bonded by the thermosetting adhesive of the present invention has good bonding performance and is convenient for later disassembly, maintenance and recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the chemical structure of the acetal structure intermediate and epoxy monomer in Example 1.

[0042] Figure 2 This is a graph showing the relationship between the bonding strength of the thermosetting adhesive containing acetal bonds in Example 1 and the change in acidity at 50°C.

[0043] Figure 3 Schematic diagram of the chemical structure of the acetal structure intermediate and epoxy monomer in Example 4. DETAILED DESCRIPTION

[0044] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0045] The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0046] Embodiment 1:

[0047] Step 1: At 90°C, p-toluenesulfonic acid monohydrate (p-TsOH·H2O) was used as a catalyst to react p-hydroxybenzaldehyde and trimethylolpropane in a mixed solution of DMF and petroleum ether at a molar ratio of 1:1.02 for 24 hours. After removing the petroleum ether, the remaining solution was dropped into a 3wt% NaHCO3 aqueous solution for precipitation. The obtained product was washed with deionized water and dried at 80°C to obtain a dihydroxy intermediate containing an acetal structure ( Figure 1 ).

[0048] Step 2: The above-synthesized monocyclic acetal dihydroxy compound and epichlorohydrin (molar ratio of 1:10) are used as raw materials, tetrabutylammonium bromide is used as a catalyst, and the reaction is carried out at 110°C for 2h for ring-opening etherification. After cooling to 50°C, 50wt% NaOH aqueous solution is added dropwise to the raw material at a molar ratio of hydroxyl to NaOH of 1:5, and the reaction is continued for 3h for ring closing. The organic phase is washed with deionized water to remove excess epichlorohydrin to obtain an epoxy monomer containing an acetal structure ( Figure 1 ).

[0049] Step 3: Add epoxy monomer containing acetal structure and isophorone diamine in a molar ratio of epoxy group to amino group of 2:1 and stir and mix them thoroughly to prepare epoxy adhesive containing acetal structure, and use it to bond carbon fiber reinforced epoxy composite material (CFRP) to prepare single lap tensile shear performance test standard specimen.

[0050] At a temperature of 50°C, 0.1, 0.5, and 1 M hydrochloric acid solutions (solvent tetrahydrofuran and water volume ratio of 9:1) were used as degradation solutions to treat the single lap tensile shear test samples bonded with the acetal bond epoxy adhesive to study the controllable debonding behavior of the adhesive under acidic conditions. The relationship between the adhesive bond strength and acidity is shown in Figure 2. Figure 2 The test sample was placed in 1M HCl (solvent V THF :V H2O =9:1) degradation solution, after 6 hours of debonding treatment, the bonding strength decreased from the initial 13.9MPa to 4.0MPa. After 10 hours of treatment, the adhesive was completely debonded and lost its bonding strength. THF :V H2O =9:1) degradation solution for 15h, the adhesive was completely debonded; in 0.1M HCl (solvent V THF :V H2O =9:1) degradation solution for 24 hours, the adhesive was completely debonded. As the concentration of hydrochloric acid increased, the time required for the adhesive to be completely debonded gradually shortened, and higher acidity could accelerate the debonding behavior of the adhesive.

[0051] Comparative Example 1:

[0052] The difference from Example 1 is that a commercial epoxy adhesive without dynamic bonds is used to explore the effect of 1 mol / L HCl (solvent V THF :V H2O =9:1) after being treated with a degradation solution, and the bonding strength test was carried out with reference to Example 1. The results are shown in Table 1. The epoxy adhesive containing an acetal structure in Example 1 has a higher initial bonding strength, and under the same degradation conditions, the epoxy adhesive containing an acetal structure in Example 1 is completely debonded, while the commercial epoxy adhesive still maintains a high bonding strength and is difficult to achieve effective debonding.

[0053] Table 1

[0054] Initial bonding strength Degradation liquid treatment 10h Example 1 Acetal-containing epoxy adhesive 13.9 MPa 0MPa Comparative Example 1 Commercial Epoxy Adhesive 10.1MPa 9.6MPa

[0055] Embodiment 2:

[0056] The epoxy monomer containing an acetal structure synthesized in Example 1 was added to 4,4'-diaminodiphenyl ether at a molar ratio of epoxy group to amino group of 2:1 and stirred thoroughly to prepare an epoxy adhesive containing an acetal structure. The epoxy adhesive was used to bond glass fiber reinforced epoxy composites (GFRP) to prepare a single lap tensile shear performance test standard specimen.

[0057] At a temperature of 50°C, a 1M hydrochloric acid solution (volume ratio of solvent acetone to water is 9:1) was used as a degradation liquid to treat the GFRP single lap tensile shear test sample bonded with an acetal bond epoxy adhesive to study the controllable debonding behavior of the adhesive under acidic conditions. After 6 hours of extended treatment with the degradation liquid, the bonding strength decreased from the initial 12.4MPa to 3.5MPa. After 10 hours of treatment, the sample was completely debonded and lost its bonding strength.

[0058] Comparative Example 2:

[0059] The difference from Example 2 is that a commercial epoxy adhesive without dynamic bonds is used to explore the effect of 1 mol / L HCl (solvent V 丙酮 :V H2O =9:1) after being treated with a degradation solution, and the bonding strength test was carried out with reference to Example 2. The results are shown in Table 2. The epoxy adhesive containing the acetal structure in Example 2 has a higher initial bonding strength, and under the same degradation conditions, the epoxy adhesive containing the acetal structure in Example 2 is completely debonded, while the commercial epoxy adhesive still maintains a relatively high bonding strength, and it is difficult to achieve controllable debonding.

[0060] Table 2

[0061] Initial bonding strength Degradation liquid treatment 10h Example 2 Acetal-containing epoxy adhesive 12.4 MPa 0MPa Comparative Example 2 Commercial Epoxy Adhesive 8.7MPa 7.9MPa

[0062] Embodiment 3:

[0063] The epoxy monomer containing an acetal structure synthesized in Example 1 was added with isophorone diamine at a molar ratio of epoxy group to amino group of 2:1 and fully stirred and mixed to prepare an epoxy adhesive containing an acetal structure. The epoxy adhesive was used to bond carbon fiber reinforced epoxy composites (CFRP) and titanium alloy (TC4) to prepare a single lap tensile shear performance test standard specimen.

[0064] At a temperature of 50°C, a 1M hydrochloric acid solution (volume ratio of solvent acetone to water is 8:2) was used as a degradation liquid to treat the CFRP / TC4 single lap tensile shear test sample bonded with an acetal structure epoxy adhesive to study the controllable debonding behavior of the adhesive under acidic conditions. After 6 hours of extended treatment with the degradation liquid, the bonding strength decreased from the initial 9.1MPa to 2.6MPa. After 10 hours of treatment, the sample was completely debonded and lost its bonding strength.

[0065] Comparative Example 3:

[0066] The difference from Example 3 is that a commercial epoxy adhesive without dynamic bonds is used to explore the effect of 1 mol / L HCl (solvent V 丙酮 :V H2O=8:2) after being treated with a degradation solution, and the bonding strength test was carried out with reference to Example 3. The results are shown in Table 3. The epoxy adhesive containing an acetal structure in Example 3 has a higher initial bonding strength, and under the same degradation conditions, the epoxy adhesive containing an acetal structure in Example 3 is completely debonded, while the commercial epoxy adhesive still maintains a relatively high bonding strength, and it is difficult to achieve controllable debonding.

[0067] Table 3

[0068] Initial bonding strength Degradation liquid treatment 10h Example 3 Acetal-containing epoxy adhesive 9.1 MPa 0MPa Comparative Example 3 Commercial Epoxy Adhesive 7.8MPa 7.0MPa

[0069] Embodiment 4:

[0070] Vanillin and glycerol were added to a mixed solution of DMF and petroleum ether in a molar ratio of 1:1, and p-toluenesulfonic acid was used as a catalyst to react at 90°C for 24 hours. After removing the petroleum ether, the remaining solution was dropped into a 3wt% NaHCO3 aqueous solution for precipitation. The obtained product was washed three times with deionized water and dried at 80°C to obtain an intermediate containing an acetal structure ( Figure 3 ). The above-synthesized monocyclic acetal dihydroxy compound and epichlorohydrin (molar ratio of 1:10) were used as raw materials, and the ring-opening etherification was catalyzed by tetrabutylammonium bromide. A 50wt% NaOH aqueous solution was added dropwise to the raw material at a molar ratio of hydroxyl to NaOH of 1:5, and the reaction was continued for 3 hours to close the ring. The organic phase was washed with deionized water to remove excess epichlorohydrin, and an epoxy monomer containing an acetal structure was obtained ( Figure 3 ).

[0071] The epoxy monomer containing an acetal structure synthesized in Example 4 was added with isophorone diamine at a molar ratio of epoxy group to amino group of 2:1 to prepare an epoxy adhesive containing an acetal structure, which was used to bond carbon fiber reinforced epoxy composites (CFRP) to prepare a single lap tensile shear performance test standard specimen.

[0072] At a temperature of 50°C, a 1M hydrochloric acid solution (the volume ratio of solvent tetrahydrofuran to water is 8:2) was used as a degradation liquid to treat the GFRP single lap tensile shear test sample bonded with an acetal structure epoxy adhesive to study the controllable debonding behavior of the adhesive under acidic conditions. After 6 hours of extended treatment with the degradation liquid, the bonding strength decreased from the initial 13.5MPa to 4.1MPa. After 12 hours of treatment, the sample was completely debonded and lost its bonding strength.

[0073] Comparative Example 4:

[0074] The difference from Example 4 is that a commercial epoxy adhesive without dynamic bonds is used to explore the effect of 1 mol / L HCl (solvent V THF :V H2O=8:2) after being treated with a degradation solution, and the bonding strength test was carried out with reference to Example 4. The results are shown in Table 4. The epoxy adhesive containing an acetal structure in Example 4 has a higher initial bonding strength, and under the same degradation conditions, the epoxy adhesive containing an acetal structure in Example 4 is completely debonded, while the commercial epoxy adhesive still maintains a relatively high bonding strength, and it is difficult to achieve controllable debonding.

[0075] Table 4

[0076] Initial bonding strength Degradation liquid treatment 12h Example 4 Acetal-containing epoxy adhesive 13.5 MPa 0MPa Comparative Example 4 Commercial Epoxy Adhesive 10.1MPa 9.8MPa

[0077] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a thermosetting adhesive with controllable debonding, characterized in that: Includes steps: S1, an aldehyde monomer and an alcohol monomer react to obtain a polyhydroxy intermediate containing an acetal structure; the aldehyde monomer has at least one hydroxyl functional group; the alcohol monomer has three or more hydroxyl functional groups; S2, epichlorohydrin and the polyhydroxy intermediate undergo ring-opening addition and ring-closing epoxidation in an alkaline environment to obtain an epoxy monomer containing an acetal dynamic bond; S3, mixing and curing the epoxy monomer obtained in step S2 with an amine curing agent to obtain a thermosetting adhesive with controllable debonding under acidic conditions.

2. The preparation method according to claim 1, characterized in that: In step S1: The aldehyde monomer includes at least one of vanillin and p-hydroxybenzaldehyde; The alcohol monomer includes at least one of glycerol, pentaerythritol, trimethylolpropane and trimethylolethane; The aldehyde monomer and the alcohol monomer are added according to a molar ratio of aldehyde group in the aldehyde monomer to the alcohol monomer of 1:1 to 1.5; The reaction temperature is 80-100°C.

3. The preparation method according to claim 1, characterized in that: In step S2: The polyhydroxy intermediate and the epichlorohydrin are added according to a molar ratio of hydroxyl groups in the polyhydroxy intermediate to the epichlorohydrin of 1:3-6; The reaction temperature of the ring-opening addition is 80 to 120°C; The temperature of the alkaline environment ring-closing epoxidation reaction is 30 to 60°C; The alkaline environment is obtained by adding an aqueous sodium hydroxide solution; The molar ratio of sodium hydroxide in the added sodium hydroxide aqueous solution to the hydroxyl group in the polyhydroxy intermediate is 4 to 10:1; The mass percentage concentration of sodium hydroxide in the sodium hydroxide aqueous solution is 30% to 60%.

4. The preparation method according to claim 1, characterized in that: In step S3: The amine curing agent includes at least one of isophorone diamine, diethylene triamine, triethylene tetramine, tetraethylene pentamine, diethyl toluene diamine, 2,4,6-tris (dimethylaminomethyl) phenol, 4,4'-diaminodiphenyl ether, and 4,4'-diaminodiphenyl sulfone; The epoxy monomer obtained in step S2 and the amine curing agent are mixed in a completely reactive stoichiometric ratio.

5. A thermosetting adhesive with controllable debonding under acidic conditions prepared according to the preparation method according to any one of claims 1 to 4.

6. Use of the controllable debonding thermosetting adhesive under acidic conditions according to claim 5 in bonding and disassembling fiber composite materials.

7. The use according to claim 6, characterized in that: When disassembling the fiber composite material bonded by the controllable debonding thermosetting adhesive under acidic conditions, the controllable debonding thermosetting adhesive under acidic conditions is treated with acid to degrade and debond the controllable debonding thermosetting adhesive under acidic conditions.

8. The use according to claim 7, characterized in that: The acid used in the acid treatment includes at least one of hydrochloric acid and sulfuric acid; The controllably debondable thermosetting adhesive under acidic conditions is treated with an acid solution containing an organic solvent.

9. The use according to claim 8, characterized in that: The organic solvent includes at least one of tetrahydrofuran, acetone and ethanol.

Citation Information

Cited By

  • Controllable depolymerization and debonding high-performance epoxy adhesive as well as preparation method and application thereof

    CN120442197A